Immune Checkpoint Inhibitors for Advanced Hepatocellular Carcinoma: Monotherapies and Combined Therapies - Ouyang, Tao; Kan, Xuefeng; Zheng, Chuansheng (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is an important cause of cancer death and is considered the 3rd most lethal around the world. Hepatectomy, liver transplantation, and ablation therapy are considered curative treatments for early-stage HCC. Transarterial chemoembolization is the preferred therapy for intermediate stage HCC. Ssystemic therapy is recommended for advanced HCC. For more than a decade, sorafenib and lenvatinib were used as the first-line treatment for the advanced HCC. For the great success of immunotherapy in melanoma and lung cancer, some immune-based treatments, such as immune checkpoint inhibitors (ICIs), have been applied in the treatment of HCC. The anti-programmed cell death protein 1 (PD1) antibodies, including nivolumab and pembrolizumab, have been approved by the Food and Drug Administration for sorafenib-pretreated patients. Moreover, due to the results of durable antitumor responses attained from the phase 3 trials, atezolizumab in combination with bevacizumab is now the standard therapy for advanced HCC. Recently, there are a lot of clinical trials involving the ICIs, as monotherapy or combination therapy, with tyrosine kinase inhibitors, antiangiogenic drugs, cytotoxic agents, and locoregional treatments, providing a promising outcome for advanced HCC. Thus, this review summarized the role of ICIs for HCC patients with monotherapy or combination therapy. The success and failures of monotherapy and combination therapy involving ICIs have provided advanced insights into HCC treatment and led to novel avenues to improve therapy efficacy in HCC.